The Legality of Gayo Customary Inheritance in the Perspective of Islamic Law - Bakri, Zaini; Saleh, Fauzi; Analiansyah, Analiansyah (Faculty of Law, Universitas Pekalongan, 2024)
The practice of inheritance distribution in the Gayo community should align with the Fiqh Mawārit, but in reality, it has not fully adhered to it. There are still deviations found in the practice of inheritance distribution, such as the belief among some community members that juelen and angkap marriages can obstruct or reduce a person's share. Given these issues, the author is interested in examining the legality of Gayo customary inheritance from the perspective of Islamic law. To address this issue, a qualitative research approach is needed, with data obtained through interviews, observations, and documentation, analyzed using social interaction theory, cultural theory, Fiqh Mawārit theory, and Maqāshid al-Syari’ah. The research results indicate that the distribution of customary inheritance in Gayo is based on the type of marriage practiced in the community. Some aspects of Gayo customary inheritance are relevant to Islamic law, while others are practiced in a deviant manner.